Recognizing and minimizing hypoglycemia: The need for individualized care. Issue 8 (6th November 2015) - Lavernia, Frank; Kushner, Pamela; Trence, Dace; Rice, Donna; Dailey, George; Kuritzky, Louis
Abstract: Hypoglycemia is a condition known to disrupt many everyday activities and is associated with increased risks of hospitalization, falls, motor vehicle accidents and mortality. Many patients with diabetes have an increased risk of hypoglycemia due to interventions targeting glycemic control. In these patients, hypoglycemia and fear of hypoglycemia may further reduce adherence to glucose-lowering regimens, contributing to the further aggravation of diabetes-related complications. Avoiding hypoglycemia should be one of the principal goals of any treatment strategies employing agents that can induce hypoglycemia in order to prevent the occurrence of associated symptoms and consequences. The education of patients and their families is an important feature of individualized management strategies in order to prevent, mitigate and treat hypoglycemic episodes. Patients with diabetes need to be made aware of how to recognize the signs of hypoglycemia and of the simple, highly effective steps that they can take to self-manage hypoglycemic episodes. Clinicians should be familiar with the risk factors for hypoglycemia, especially the profiles of the different classes of glucose-lowering medications such as the sulfonylureas and insulin. This article aims to review the risk factors for hypoglycemia and its implications for patients and healthcare systems, and provide practical advice for minimizing the risk of hypoglycemia and its consequences.